Labour Market Participation of Older Workers: Drivers and Obstacles - Ulrich Walwei; Jürgen Deller (Intereconomics, 2021)
From an international comparative point of view the paper deals with driving forces and potential obstacles for the labour market participation of older workers. It goes into depth by focusing on four case studies that seem to be typical for different contexts. Germany, Israel, Italy and Sweden were selected in order to examine the development and the situation of older workers in detail. Each country stands for a specific configuration, e.g. because it may represent a trend reversal, a continuously outstanding performance, or lasting problems. The cases also provde information on pension reforms and approaches to better manage ageing workforces, in some cases including a new balance of work and retirement. Being aware of the different country situations, it becomes obvious that one size of politics does not fit all. Independent of national policies, employability over the life cycle should gain more attention. Regarding future developments, continuous skill improvement and a healthy work environment are indispensable to keep older workers in work.
Keywords: 330